Faktor-Faktor Yang Mempengaruhi Literasi Fintech Syariah Pada Kalangan Mahasiswa - Silviana Rizqi Safitri; Silviana Pebruary (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the factors that influence Islamic fintech literacy among university students, focusing on three main variables: gender, Islamic financial education, and social media. Islamic fintech is rapidly developing as an alternative to digital financial services that comply with Islamic principles. However, students' literacy levels regarding these services are still relatively low. This study uses a quantitative approach with a survey method through a Google Form-based questionnaire and involves 170 students from various regions in Indonesia. The data is analyzed using multiple linear regression. The results show that Islamic financial education and social media have a positive and significant effect on Islamic fintech literacy. Conversely, gender does not show a significant effect. These findings indicate that improving Islamic fintech literacy among students can be achieved through strengthening Islamic-based financial education and optimizing social media as an educational too. Keywords: literasi fintech syariah, jenis kelamin, pendidikan keuangan syariah, media sosial, mahasiswa.